Electrically Scaled Hafnium Oxide Based Ge Devices. (19th August 2016) - Tapily, Kandabara; Dey, Sonal; Consiglio, Steven; Clark, Robert D.; Wajda, Cory S.; Leusink, Gert J.; Diebold, Alain C.
Abstract : Hfx Zr1-x O2 (0≤x≤1) films with different Hf/(Hf+Zr) ratios were deposited on Al2 O3 passivated Ge by atomic layer deposition (ALD) combined with a cyclical deposition and annealing scheme (termed DADA) in which an annealing was performed after every 20 ALD cycles. A post microwave plasma treatment was conducted after the high-k deposition. Metal oxide semiconductor capacitors (MOSCAPs) using ALD TiN metal gates were fabricated to investigate the electrical properties of the ALD Hfx Zr1-x O2 thin films. The electrical measurements show significant electrical benefits compared to samples that were not deposited using method described above. The electrical results were corroborated by synchrotron X-ray diffraction measurement